James Dodge papers - Dodge, James (Surgeon)
Volume containing sick reports for sailors on the frigates Congress and Constitution.
Surgeon, U.S. Navy.
Collection material in English.
Keywords: Congress (Frigate: 1794-1834); Constitution (Frigate); United States. -- Navy -- Medical care -- 19th century; Ship's papers -- 19th century; Surgeons